Nutritional considerations in high performance youth soccer: a systematic review - North, M.; Kelly, A. L.; Ranchordas, M. K.; Cole, M. (Journal of Science in Sport and Exercise, 2022)
Purpose: As players in high performance youth soccer (HYPS) environments undergo large changes in growth and maturation throughout the course of their development, they require specific nutritional intakes if they are to meet these demands. The purpose of this review was to synthesise current nutritional research conducted within HYPS players. Methods: A systematic approach, following PRISMA guidelines, was employed to capture all articles related to nutrition within HPYS using the databases MEDLINE and SPORTDiscus. Study quality and risk of bias were assessed using a Downs and Black instrument. Observational and intervention studies which investigated an element of nutritional status, knowledge, or intervention in academy aged players (U9 to U23s) within HPYS settings were included. Results: Fifty-three articles qualified assessing: current nutritional intake and energy balance (n = 21); ergogenic aids/supplements (n = 13); hydration status (n = 6); the influence of Ramadan fasting (n = 4); Vitamin D status (n = 4); female HPYS players (n = 3); nutrition knowledge (n = 2). Outcomes demonstrate a large proportion of HPYS players exhibit insufficient energy and carbohydrate intake, and a lack sufficient periodisation of nutrition to account for varying training/match loads. Large variability in energy intake and expenditure exists between and within chronological age groups, indicating the potential impact on growth and maturation. Female HPYS data is lacking but indicates similar trends to male counterparts. Conclusion: HYPS players do not currently meet their energy requirements however the impact of growth and maturation is not fully understood. Furthermore, within this demographic future research is required into the barriers and enablers of players achieving adequate energy intake.